Isolasi dan Pertumbuhan Mikroba dari Tanah menggunakan Media Berbasis Ekstrak Singkong - Dian Novita; Ardi Mustakim (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to explore the potential of cassava extract (Manihot esculenta)-based growth media for isolating microorganisms from soil. The use of alternative culture media is crucial, especially in regions with limited access to commercial media such as Nutrient Agar or Potato Dextrose Agar, which are relatively expensive. Cassava, a tropical tuber rich in starch and widely available in Indonesia, offers significant promise as a natural substrate for microbial growth. Microbial isolation was performed using a serial dilution method on soil samples collected from an organic garden. The media was prepared from cassava juice mixed with agar and glucose, sterilized, and poured into petri dishes. After inoculation, microbes were incubated for seven days at room temperature. Colony morphology was observed macroscopically, and Gram staining was used to identify bacterial characteristics. The results revealed that cassava extract media effectively supported the growth of diverse microbial colonies, varying in shape, color, and edge structure. Most isolates were identified as Gram-positive, with rod and coccus forms. The presence of pigmented colonies indicates the potential of certain isolates to produce bioactive compounds. In conclusion, cassava extract-based media is a viable alternative for soil microbiology studies. It is not only cost-effective but also facilitates the exploration of local microbial diversity with potential applications in biotechnology, including bioremediation and enzyme production. This approach encourages the use of indigenous resources in scientific research, promoting sustainability and accessibility in microbiological practices.